Barium titanate-barite composite material as well as preparation method and application thereof
Through the proportion and preparation method of titanic acid-heavy crystal composite materials, the lack of existing radiation protection materials in the face of modern multifunctional, environmental protection, and economy requirements, and realized high-agent constant, excellent anti-radiation resistance, anti-radiation resistance Performance, good mechanical strength and economic effects.
Patent Information
- Application Number
- CN202411527986.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing radiation protection materials such as barium titanate, barite and lead plates have problems such as high production costs, easy deterioration, high weight, high construction difficulty and potential environmental threats when facing modern multifunctional, environmentally friendly and economic requirements.
Using titanic acid-composite material, through a reasonable ratio of titanic acid, sulfate with different particle size, coupling agent and nano-fillers, prepare high-agency constant, excellent radiation resistance, good mechanical strength and good mechanical strength and good mechanical strength and good mechanical strength and good mechanical strength and good mechanical strength and strength strength and good mechanical strength and intensity of mechanical strength and strength. Economic characteristics of composite materials.
The high performance and economy of materials have been realized, the production cost is reduced, the construction process is simplified, suitable for large -scale applications, while maintaining high performance, it realizes surface flatness and aesthetics, significantly improved construction efficiency.
Smart Images

Figure BDA0005111320650000101 
Figure BDA0005111320650000111 
Figure BDA0005111320650000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic materials, and in particular to a barium titanate-baryte composite material and a preparation method and application thereof. Background Art
[0002] With the continuous advancement of technology and the increasing complexity of the application environment, the performance requirements for materials are also constantly increasing, especially in the fields of construction, industry and electronics, materials with both high dielectric constant and radiation resistance have become an urgent need in the market. Although traditional radiation protection materials, such as barium titanate, barite and lead plates, have shown certain advantages in their respective applications, they also face their own limitations and are difficult to fully meet the diverse needs of modern applications.
[0003] Barium titanate is widely used in capacitors, piezoelectric elements and electromagnetic shielding materials due to its high dielectric constant and low dielectric loss. However, its high production cost and easy degradation in high radiation environments make it difficult to promote in large-scale applications. At the same time, barium titanate materials are usually made into powders or blocks, which makes it difficult to maintain surface flatness and aesthetics in large-area applications, increasing the complexity and cost of construction. Barite materials are widely used in X-ray shielding and nuclear industry protection due to their high density and excellent radiation resistance. However, the low dielectric constant of barite materials limits their use in electronic applications that require high dielectric properties. In addition, barite materials themselves are relatively fragile and difficult to achieve smooth and flat surfaces. Additional surface treatment is usually required, which not only increases processing costs but also reduces construction efficiency. Lead sheet materials have been widely used in the medical and nuclear industries due to their high density and excellent radiation shielding capabilities. However, lead sheets are heavy and difficult to construct, especially in large-area applications, and the transportation and installation costs are extremely high. In addition, the toxicity of lead poses a potential threat to the environment and human health, which not only limits its scope of application, but also requires that lead sheets in many cases must be covered with additional decorative layers to improve their aesthetics, further increasing costs and complexity.
[0004] Therefore, although the above-mentioned traditional materials have certain advantages in certain specific applications, they have obvious defects when facing modern multifunctional, environmental protection and economic requirements. Summary of the invention
[0005] The object of the present invention is to provide a barium titanate-baryte composite material and a preparation method and application thereof, wherein the barium titanate-baryte composite material has high performance, functionality, environmental protection and economic requirements.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a barium titanate-baryte composite material, comprising the following raw materials in percentage by weight:
[0008] Barium titanate 20-30.5%, first barium sulfate 35-45%, second barium sulfate 25-35%, coupling agent, nano silicon dioxide 0.5-2%, nano aluminum oxide 0.5-2%;
[0009] The average particle size of the first barium sulfate is 4 to 5 μm, and the maximum particle size is ≤27 μm; the average particle size of the second barium sulfate is 3 to 4.5 μm, and the maximum particle size is ≤24 μm;
[0010] The coupling agent is a titanate coupling agent or a silane coupling agent;
[0011] When the coupling agent is a titanate coupling agent, the mass percentage of the titanate coupling agent is 1 to 3%;
[0012] When the coupling agent is a silane coupling agent, the mass percentage of the silane coupling agent is 0.5-2%.
[0013] Preferably, the titanate coupling agent includes one or more of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, tetraoctyl titanate and tetraphenyl titanate.
[0014] Preferably, the silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, vinyltriethoxysilane, epoxypropyltrimethoxysilane and isocyanatepropyltriethoxysilane.
[0015] The present invention provides a method for preparing the barium titanate-baryte composite material described in the above technical solution, comprising the following steps:
[0016] The barium titanate, the first barium sulfate, the second barium sulfate, the coupling agent, the nano silicon dioxide and the nano aluminum oxide are mixed by ball milling to obtain a mixed material;
[0017] The mixed material is spray-granulated to obtain a spherical material;
[0018] The spherical material is pressed and formed by isostatic pressing to obtain a green body;
[0019] The green body is sintered in a protective atmosphere to obtain a barium titanate-baryte composite material.
[0020] Preferably, the ball milling mixing time is 2 to 4 hours, and the rotation speed is 150 to 200 rpm.
[0021] Preferably, the spray granulation conditions include: a feed rate of 10 to 20 mL / min, and a spray drying temperature of 120 to 150°C.
[0022] Preferably, the particle size of the spherical material is 100-300 μm.
[0023] Preferably, the compression molding conditions include: a pressure of 250-350 MPa, a mold temperature of 20-40° C., and a time of 10-15 min.
[0024] Preferably, the sintering temperature is 1250-1350° C., and the holding time is 4-6 hours; the protective atmosphere includes nitrogen or argon.
[0025] The present invention provides the application of the barium titanate-baryte composite material described in the above technical solution or the barium titanate-baryte composite material prepared by the preparation method described in the above technical solution in the fields of architectural decoration, industrial protection or electronic components.
[0026] The present invention provides a barium titanate-baryte composite material. The present invention selects barium titanate and barium sulfate of different specifications as main raw materials, composites barium titanate with barite, and ensures the high performance and production economy of the composite material through reasonable proportioning and the addition of auxiliary materials. The components in the barium titanate-baryte composite material of the present invention work synergistically to ensure the high performance and economy of the barium titanate-baryte composite material. Barium titanate, as the main raw material, provides high dielectric constant and low dielectric loss, and improves the application performance of the material in electronic components; the first barium sulfate enhances the radiation resistance and mechanical strength with a larger particle size and high purity, while the finer particle size of the second barium sulfate improves the compactness and mechanical stability of the material; the titanate coupling agent enhances the interface bonding force of the composite material by reacting with the surface of barium titanate, and the silane coupling agent improves the adhesion of barium sulfate to other components by chemical bonding; nano-silicon dioxide and aluminum oxide further improve the mechanical properties and heat resistance of the material. The synergistic effect of the above components of the present invention not only gives the material excellent dielectric and radiation resistance, but also improves its mechanical strength and production economy, while ensuring that the material is easy to construct and suitable for large-scale applications. Therefore, the present invention greatly improves the dielectric constant, dielectric loss and radiation resistance of the material by adding barium titanate. After barium titanate is compounded with barite, the electrical properties and interface bonding strength of the material are significantly improved.
[0027] The barium titanate-baryte composite material of the present invention has high dielectric constant, excellent radiation resistance, good mechanical strength, economy and construction convenience, and is particularly suitable for the fields of building decoration, industrial protection, electronic components, and is especially suitable for occasions requiring high dielectric constant and radiation resistance, such as radiation shielding plates, dielectric materials of electronic devices, etc.
[0028] The barium titanate-baryte composite material of the present invention can be made into large-sized plates of 400×800 mm. The surface is precisely formed and polished, and has good flatness and aesthetics, and is suitable for large-area laying like ceramic tiles. The present invention combines high performance with aesthetics, which not only improves the radiation resistance, but also effectively reduces the production cost. While maintaining high performance, it achieves the dual requirements of surface flatness and aesthetics, simplifies the construction process, and can meet a variety of application needs.
[0029] The barium titanate-baryte composite material of the present invention has the characteristic of convenient construction because it can be made into large-sized plates, and after precision molding and polishing, the surface is flat and smooth, suitable for large-area paving, and reduces the construction adjustment work. In addition, the high mechanical strength and density of the material ensure that it is not easy to break or damage during the installation process, reducing the difficulty of construction; the material has good dimensional stability, and the polished surface does not require additional treatment, which simplifies the construction process. At the same time, compared with traditional radiation shielding materials such as lead plates, the composite material is lighter in weight, easy to transport and install, and further improves the construction efficiency. Therefore, compared with traditional materials, the barium titanate-baryte composite material of the present invention shows significant advantages in functionality, environmental protection and construction convenience, providing a more extensive and cost-effective solution for modern construction and industrial applications, and has great market application prospects. DETAILED DESCRIPTION
[0030] The present invention provides a barium titanate-baryte composite material, comprising the following raw materials in percentage by weight:
[0031] Barium titanate 20-30.5%, first barium sulfate 35-45%, second barium sulfate 25-35%, coupling agent, nano silicon dioxide 0.5-2%, nano aluminum oxide 0.5-2%;
[0032] The average particle size of the first barium sulfate is 4 to 5 μm, and the maximum particle size is ≤27 μm; the average particle size of the second barium sulfate is 3 to 4.5 μm, and the maximum particle size is ≤24 μm;
[0033] The coupling agent is a titanate coupling agent or a silane coupling agent;
[0034] When the coupling agent is a titanate coupling agent, the mass percentage of the titanate coupling agent is 1 to 3%;
[0035] When the coupling agent is a silane coupling agent, the mass percentage of the silane coupling agent is 0.5-2%.
[0036] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.
[0037] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided by the present invention include 20-30.5% barium titanate, preferably 22-28%, and more preferably 24-25%. The barium titanate of the present invention has a high dielectric constant, which can generate polarization under an external electric field, thereby improving the dielectric properties of the composite material while maintaining low dielectric loss.
[0038] Calculated by mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided by the present invention include 35-45% of the first barium sulfate, and more preferably 38-40%.
[0039] In the present invention, the average particle size of the first barium sulfate is 4-5 μm, and the maximum particle size is ≤27 μm.
[0040] In the present invention, the barium sulfate content in the first barium sulfate is preferably ≥90wt%, the whiteness of the first barium sulfate is preferably 83-84%, more preferably 83.8%, and the pseudo specific gravity is preferably 0.65-0.75g / cm 3 , more preferably 0.69 g / cm 3 .
[0041] The present invention has no special limitation on the source of the first barium sulfate, and any commercially available product that meets the above purity is known in the art; in the embodiment of the present invention, the first barium sulfate is specifically GY-1250, produced by Jiangxi Guangyuan Chemical Co., Ltd. The first barium sulfate of the present invention has a high barium content and excellent whiteness, as well as high density and good X-ray shielding effect, which can enhance the electrical properties and radiation resistance of the material, especially in applications requiring high density and high purity. In addition, the larger particle size and high purity of the first barium sulfate help to improve the overall mechanical strength and stability of the composite material as well as the radiation shielding performance.
[0042] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided by the present invention include 25-35% of the second barium sulfate, preferably 27-32%, and more preferably 29-30%.
[0043] In the present invention, the average particle size of the second barium sulfate is 3-4.5 μm, and the maximum particle size is ≤24 μm.
[0044] In the present invention, the content of barium sulfate in the second barium sulfate is preferably ≥90wt%, the whiteness of the second barium sulfate is preferably 85-86%, more preferably 85.4%, and the specific gravity is preferably 0.65-0.75g / cm 3 , more preferably 0.68 g / cm 3 .
[0045] The present invention does not specifically limit the source of the second barium sulfate, and any commercially available product that meets the above purity is known in the art; in the embodiments of the present invention, it is specifically barium sulfate (GY-2500), Jiangxi Guangyuan Chemical Co., Ltd. The second barium sulfate of the present invention has a fine particle size and a good particle size distribution to improve the density and mechanical strength of the material. In the present invention, the second barium sulfate has a fine particle size and a uniform particle size distribution. Such fine particles can effectively fill the tiny gaps in the material, significantly improve the density of the material, and reduce the porosity. By improving the density of the material, the overall mechanical strength of the composite material is enhanced, making it more durable and stable, and is particularly suitable for application scenarios that require high strength and surface flatness.
[0046] Measured by mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided by the present invention include a coupling agent; the coupling agent is a titanate coupling agent or a silane coupling agent.
[0047] When the coupling agent is a titanate coupling agent, the mass percentage of the titanate coupling agent is 1-3%, preferably 2-2.8%, and more preferably 2.2-2.5%; the titanate coupling agent preferably includes one or more of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, tetraoctyl titanate and tetraphenyl titanate; when the titanate coupling agent is two or more of the above, the present invention has no special limitation on the ratio of different types of titanate coupling agents, and any ratio is acceptable. The present invention utilizes a titanate coupling agent to improve the interfacial bonding force between barium titanate and other inorganic components. The titanate coupling agent can react with the surface of barium titanate, combine with titanium ions through chemical bonds, and form a chemical bonding layer at the interface of the material. This improvement in interfacial bonding force helps to improve the mechanical properties of the composite material, such as compressive strength and flexural strength. Reaction mechanism: The titanate coupling agent can be hydrolyzed in a wet environment to form a titanium oxide layer, which can improve the adhesion and interaction between barium titanate and barium sulfate, and ultimately enhance the overall structure of the composite material.
[0048] When the coupling agent is a silane coupling agent, the mass percentage of the silane coupling agent is 0.5-2%, preferably 1.0-1.5%; the silane coupling agent preferably includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane (APTES), vinyltriethoxysilane (VTES), epoxypropyltrimethoxysilane (GPTMS) and isocyanatepropyltriethoxysilane (IPTES); when the silane coupling agent is two or more of the above, the present invention has no special restrictions on the ratio of different types of silane coupling agents, and any ratio is acceptable. The present invention uses a silane coupling agent as a bridging material, which can connect inorganic components (barium sulfate, barium titanate) to an organic matrix through a silicon-oxygen bond; the silane coupling agent reacts with the surface of the inorganic material to form a chemical bond, thereby improving the interface bonding force between the inorganic material and other components. Reaction mechanism: Silane coupling agent hydrolyzes on the surface of the material to form silanol groups, which then undergo condensation reaction with the surface of barium sulfate or barium titanate to form strong silicon-oxygen bonds. This chemical reaction can enhance the interfacial strength of the composite material, thereby improving the mechanical properties and radiation resistance of the material.
[0049] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided by the present invention include 0.5-2%, preferably 0.8-1.8%, and more preferably 1-1.5% of nano-silicon dioxide, and the particle size of the nano-silicon dioxide is preferably 20-40nm, and more preferably 30nm. The present invention utilizes nano-silicon dioxide to improve the mechanical strength, compactness and radiation resistance of the material. Nano-silicon dioxide can fill the tiny pores in the material due to its extremely small particle size, thereby improving the density and mechanical strength of the material. It can also enhance the radiation resistance of the material by interacting with other components (such as barium titanate and barium sulfate).
[0050] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided by the present invention include 0.5-2%, preferably 1-1.5% of nano-alumina; the particle size of the nano-alumina is preferably 30-50nm, more preferably 40-45nm. The present invention uses nano-alumina to further enhance the mechanical properties and thermal stability of the material. Nano-alumina has excellent heat resistance and mechanical properties, can enhance the high temperature resistance of the composite material, and improve the hardness and strength of the material. Its interaction with barium titanate and barium sulfate allows the material to remain stable even at high temperatures.
[0051] The present invention achieves the following effects by rationally compounding barium titanate, barium sulfate of different particle sizes, a coupling agent and nanofillers (such as silicon dioxide and aluminum oxide):
[0052] High dielectric constant: The addition of barium titanate gives the composite material a high dielectric constant, making it suitable for use as a dielectric material.
[0053] Radiation resistance: The synergistic effect of barium sulfate (especially high-density first barium sulfate) and nanofillers greatly improves the radiation resistance of the material, making it suitable for use in radiation shielding panels.
[0054] Mechanical strength and density: By controlling the particle size distribution of barium sulfate and adding nanofillers, the composite material has higher mechanical strength and density, ensuring its stability under high load conditions.
[0055] Economy and construction convenience: By rationally proportioning various raw materials, the composite material of the present invention not only achieves a high level of performance, but also has a relatively low production cost. In particular, the material can be processed into large-area flat plates, making it simple and easy to construct.
[0056] The present invention provides a method for preparing the barium titanate-baryte composite material described in the above technical solution, comprising the following steps:
[0057] The barium titanate, the first barium sulfate, the second barium sulfate, the coupling agent, the nano silicon dioxide and the nano aluminum oxide are mixed by ball milling to obtain a mixed material;
[0058] The mixed material is spray-granulated to obtain a spherical material;
[0059] The spherical material is pressed and formed by isostatic pressing to obtain a green body;
[0060] The green body is sintered in a protective atmosphere to obtain a barium titanate-baryte composite material.
[0061] In the present invention, before ball milling and mixing, the barium titanate, the first barium sulfate and the second barium sulfate are preferably vacuum dried in a vacuum drying oven to remove moisture from the raw materials and prevent bubbles or pores from being generated during molding and sintering; the vacuum drying temperature is preferably 100° C. and the time is preferably 4 hours.
[0062] In the present invention, the ball milling time is preferably 2 to 4 hours, more preferably 2.5 to 3 hours, and the rotation speed is preferably 150 to 200 rpm, more preferably 160 to 180 rpm. In the present invention, the ball milling method is preferably dry ball milling. During ball milling, ethanol (5 wt% of the total material) can be preferably added as a dispersant to improve the uniformity of the powder.
[0063] In the present invention, the spray granulation is preferably carried out using a spray granulator; the conditions of the spray granulation preferably include: a feed rate of 10 to 20 mL / min, more preferably 12 to 15 mL / min, a spray drying temperature of 120 to 150° C., preferably 130 to 140° C.; the particle size of the spherical material is preferably 100 to 300 μm, preferably 120 to 250 μm, more preferably 150 to 200 μm, and further preferably 160 to 180 μm.
[0064] After the spray granulation is completed, the obtained powder particles are left to stand at room temperature for 24 hours to ensure the uniformity and stability of the particles, which helps to improve the effect of subsequent compression molding.
[0065] In the present invention, the conditions for the compression molding include: a pressure of 250-350 MPa, more preferably 300-320 MPa, a mold temperature of 20-40°C, and a time of 10-15 min, preferably 12-13 min. The present invention preferably uses an isostatic press for compression molding, and the above compression conditions ensure the density and uniformity of the plate.
[0066] In the present invention, during the press molding, the present invention has no special limitation on the pressing molding size, which can be adjusted according to actual needs; in the embodiment of the present invention, the specific mold used for pressing the blank is 412×824mm (considering a 3% shrinkage rate).
[0067] 1. Ensure that the finished product size meets the requirements: When pressed, the green body size is 412×824mm. Considering the shrinkage characteristics of the material during the sintering process, the size after sintering is expected to be 400×800mm. This shrinkage rate of about 3% is based on the optimization result of the thermal expansion coefficient of the material and the sintering process, ensuring that the final finished product size meets the expected standard specifications. This dimensional accuracy is crucial for laying and installation in practical applications, especially when laying over a large area.
[0068] 2. Ensure the density and strength of the material: During the sintering process, the green body undergoes microstructural rearrangement and densification, resulting in a reduction in size. By controlling the initial size of the green body, it is possible to ensure that the material is dense and free of pores after sintering, thereby improving mechanical strength and radiation resistance. The finished product size is smaller than the green body size, indicating that the material has achieved a good densification effect during the sintering process, which helps to improve its mechanical properties and durability.
[0069] Therefore, ensuring that the size after sintering is smaller than the green body size not only reflects the normal shrinkage characteristics of the material, but also ensures the mechanical strength, density and dimensional accuracy of the finished product, making it suitable for large-scale industrial applications.
[0070] After the compression molding is completed, the present invention preferably performs demoulding, and compressed air is used to assist demoulding to avoid damage to the surface of the plate or stress concentration.
[0071] In the present invention, the sintering temperature is preferably 1250-1350°C, more preferably 1300°C, and the holding time is preferably 4-6 hours, more preferably 5 hours; the protective atmosphere preferably includes nitrogen or argon to avoid oxidation or uneven chemical reaction at high temperature. The present invention adopts the above sintering conditions to ensure uniform sintering of the plate inside and outside to form a dense microstructure.
[0072] After the sintering is completed, the present invention preferably cools down to room temperature to reduce warping or cracking caused by thermal stress; the cooling rate is preferably 5-8°C / h, more preferably 6-8°C / h.
[0073] During the sintering process, the plate is placed on a support frame or a high-temperature resistant plate to avoid bending or deformation due to its own weight and ensure the flatness and stability of the plate.
[0074] After the sintering, the present invention preferably performs surface polishing and size trimming on the obtained plate in sequence to make the plate size meet the requirements. The present invention preferably performs polishing on the plate surface by a water polishing machine to ensure the flatness and smoothness of the plate surface, and the surface polishing is preferably performed using 800-1000 mesh fine sandpaper.
[0075] The present invention preferably uses precision cutting technology to trim the plate, controls the tool linear speed and the use of cooling water during the cutting process to avoid cracks or thermal deformation, and ensures that the final size meets the required requirements. The tool linear speed is preferably 20-30m / min, and the feed rate is 0.1-0.5mm / s to ensure cutting accuracy and surface quality. The flow rate of the cooling water is preferably 10-20L / min, the water pressure is preferably 0.5-1MPa, and the water temperature is preferably 15-25°C to effectively cool the cutting area and prevent overheating and material damage. The present invention controls the above-mentioned cutting parameters to ensure high efficiency and precision during the cutting process to avoid cracks and thermal damage.
[0076] The present invention preferably determines the size after sintering according to the actual application requirements and the optimization of material properties; in the embodiment of the present invention, it is specifically 400×800mm. The size after sintering is determined according to the following methods: 1) The requirements of the application field: The plate size of 400×800mm meets the standard specifications in the fields of architectural decoration and industrial protection. This size is suitable for large-area paving, such as radiation shielding panels or wall decoration materials, which can effectively reduce the number of splicing times and improve construction efficiency. In addition, this size is also convenient for transportation and installation, suitable for industrial production and on-site construction. 2) Balance of material properties: By controlling the size after sintering, the balance between thickness, density, mechanical strength and flatness of the plate can be ensured. The dimensional change during the sintering process is closely related to the density and uniformity of the material. Selecting this size can ensure that the material maintains good surface smoothness and stability while ensuring mechanical strength and radiation resistance. 3) Processing and production feasibility: The size of 400×800mm can be efficiently produced in current industrial equipment, and the dimensional tolerance of the finished product is controlled by precision cutting technology to meet strict quality standards. In addition, this size is also conducive to subsequent precision polishing and finishing to ensure that the material surface reaches the ideal flatness. Therefore, the size standard of 400×800mm is determined based on multiple factors such as application requirements, material performance optimization and production feasibility to ensure that the material has good performance in practical applications.
[0077] The present invention provides the application of the barium titanate-baryte composite material described in the above technical solution or the barium titanate-baryte composite material prepared by the preparation method described in the above technical solution in the fields of architectural decoration, industrial protection or electronic components. The present invention has no particular limitation on the method of the application, and the barium titanate-baryte composite material can be used in the above fields according to methods well known in the art.
[0078] The barium titanate-baryte composite material of the present invention is particularly suitable for occasions requiring high dielectric constant and radiation resistance, such as radiation shielding plates, dielectric materials of electronic devices, etc.
[0079] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0080] In the following embodiments, the first barium sulfate is specifically barium sulfate (GY-1250) commercially available from Jiangxi Guangyuan Chemical Co., Ltd.; the second barium sulfate is specifically barium sulfate (GY-2500) commercially available from Jiangxi Guangyuan Chemical Co., Ltd., and specific parameters are shown in Table 1.
[0081] Table 1 Performance parameters of the first barium sulfate GY-1250 and the second barium sulfate GY-2500
[0082]
[0083]
[0084] Example 1
[0085] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided in this embodiment are:
[0086] Barium titanate (BaTiO3): 28wt%; first barium sulfate: 40wt%; second barium sulfate: 27wt%; titanate coupling agent (tetrabutyl titanate): 2wt%; nano-silicon dioxide: 1wt% (particle size is 20nm); nano-aluminum oxide: 2wt% (particle size is 30nm).
[0087] The preparation method of the barium titanate-baryte composite material is as follows: barium titanate, a first barium sulfate and a second barium sulfate are vacuum dried in a vacuum drying oven at 100° C. for 4 hours, the dried barium titanate and barium sulfate are mixed with a titanate coupling agent, nano-silicon dioxide (with a particle size of 20 nm) and nano-alumina (with a particle size of 30 nm) in a ball mill in proportion, the mixing time is 3 hours, the rotation speed is 180 rpm, a uniform mixture is obtained, the obtained mixture is spray granulated by a spray granulator, the feed rate of the spray granulation is 15 mL / min, the spray drying temperature is 130° C., spherical particles with a particle size of 150 μm are obtained, and the obtained spherical particles are allowed to stand at room temperature for 24 hours;
[0088] The spherical particles were pressed into shape by isostatic pressing method, with a mold temperature of 40°C and a pressure of 300 MPa. The initial size of the mold was 412×824 mm, the molding time was 12 min, and compressed air was used to assist demolding to obtain a green body.
[0089] The green body was placed on a support frame and placed in a sintering furnace. It was sintered in a nitrogen protective atmosphere at a sintering temperature of 1300°C and a holding time of 5 hours. After sintering, the temperature was cooled to room temperature at a cooling rate of 6°C / h. The surface was polished using 800-mesh fine sandpaper and a water-polishing machine. The plate was precisely cut to a size of 400×800mm.
[0090] Example 2
[0091] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided in this embodiment are:
[0092] Barium titanate (BaTiO3): 25wt%; first barium sulfate: 40wt%; second barium sulfate: 30wt%; titanate coupling agent (tetrabutyl titanate): 2wt%; nano-silicon dioxide: 1wt% (particle size is 30nm); nano-aluminum oxide: 2wt% (particle size is 40nm).
[0093] Preparation method:
[0094] After the barium titanate, the first barium sulfate and the second barium sulfate were vacuum dried in a vacuum drying oven at 100° C. for 4 hours, the barium titanate, the barium sulfate, the titanate coupling agent, the nano-silicon dioxide (with a particle size of 30 nm) and the nano-alumina (with a particle size of 40 nm) were mixed in a ball mill in proportion for 3 hours at a rotation speed of 180 rpm to obtain a uniform mixed material;
[0095] The obtained mixture was spray granulated by a spray granulator, the feed rate of the spray granulation was 15 mL / min, the spray drying temperature was 130°C, and spherical particles with a particle size of 150 μm were obtained, and the spherical particles were left to stand at room temperature for 24 hours;
[0096] The spherical particles were pressed into shape by isostatic pressing method, with a mold temperature of 40°C and a pressure of 300 MPa. The initial size of the mold was 412×824 mm, the molding time was 12 min, and compressed air was used to assist demolding to obtain a green body.
[0097] The green body was placed on a support frame and placed in a sintering furnace. It was sintered in a nitrogen protective atmosphere at a sintering temperature of 1300°C and a holding time of 5 hours. After sintering, the temperature was cooled to room temperature at a cooling rate of 6°C / h. The surface was polished using 800-mesh fine sandpaper and a water-polishing machine, and finally precisely cut to a standard size of 400×800mm.
[0098] Example 3
[0099] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided in this embodiment are:
[0100] Barium titanate (BaTiO3): 30.5wt%; first barium sulfate: 35wt%; second barium sulfate: 29wt%; silane coupling agent (γ-aminopropyltriethoxysilane): 2.0wt%; nano-silicon dioxide: 2wt% (particle size is 40nm); nano-alumina: 1.5wt% (particle size is 50nm);
[0101] Preparation method:
[0102] The barium titanate, the first barium sulfate and the second barium sulfate are dried in a vacuum oven at 100° C. for 4 hours, and then the dried barium titanate and barium sulfate are mixed with a silane coupling agent, nano silicon dioxide (with a particle size of 40 nm) and nano aluminum oxide (with a particle size of 50 nm) in a ball mill according to a proportion, and the mixing time is 3 hours at a rotation speed of 180 rpm to obtain a uniform mixed material;
[0103] The obtained mixture was spray granulated by a spray granulator, the feed rate of the spray granulation was 20 mL / min, the spray drying temperature was 150°C, and spherical particles with a particle size of 200 μm were obtained, and the spherical particles were allowed to stand at room temperature for 24 hours;
[0104] The spherical particles were pressed into shape by isostatic pressing method, with a mold temperature of 40°C and a pressure of 350 MPa. The initial size of the mold was 412×824 mm, the molding time was 15 min, and compressed air was used to assist demolding to obtain a green body.
[0105] The green body was placed on a support frame and placed in a sintering furnace. It was sintered in a nitrogen protective atmosphere at a sintering temperature of 1300°C and a holding time of 4 hours. After sintering, the temperature was cooled to room temperature at a cooling rate of 5°C / h. The surface was polished with 800-mesh fine sandpaper and precisely cut into 400×800mm plates.
[0106] Example 4
[0107] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided in this embodiment are:
[0108] Barium titanate (BaTiO3): 22wt%; first barium sulfate: 45wt%; second barium sulfate: 27wt%; titanate coupling agent (tetraethyl titanate): 2.2wt%; nano-silicon dioxide: 1.8wt% (particle size is 30nm); nano-aluminum oxide: 2wt% (particle size is 45nm);
[0109] Preparation method:
[0110] After vacuum drying barium titanate, the first barium sulfate and the second barium sulfate at 100° C. for 4 hours, the barium titanate, barium sulfate, titanate coupling agent, nano silicon dioxide (particle size of 30 nm) and nano aluminum oxide (particle size of 45 nm) are mixed in a ball mill in proportion, the mixing time is 2.5 hours, the rotation speed is 170 rpm, and a uniform mixed material is obtained;
[0111] The obtained mixture was spray granulated by a spray granulator, the feed rate of the spray granulation was 12 mL / min, the spray drying temperature was 140°C, and spherical particles with a particle size of 120 μm were obtained, and the spherical particles were allowed to stand at room temperature for 24 hours;
[0112] The isostatic pressing method was adopted, the mold temperature was 40°C, the spherical particles were pressed into shape at a pressure of 250 MPa, the initial size of the mold was 412×824 mm, the molding time was 10 min, and compressed air was used to assist demolding to obtain a green body.
[0113] The green body was placed on a support frame and placed in a sintering furnace. It was sintered in a nitrogen protective atmosphere at a sintering temperature of 1300°C and a holding time of 6 hours. After sintering, the temperature was cooled to room temperature at a cooling rate of 5°C / h. The surface was polished using 800-mesh fine sandpaper using a water-polishing machine and precisely cut into finished products of 400×800mm.
[0114] Example 5
[0115] In terms of mass percentage, the raw materials for preparing the barium titanate-baryte composite material provided in this embodiment are:
[0116] Barium titanate (BaTiO3): 24wt%; first barium sulfate: 38wt%; second barium sulfate: 32wt%; silane coupling agent (γ-aminopropyltriethoxysilane): 2wt%; nano-silicon dioxide: 2wt% (particle size is 20nm); nano-aluminum oxide: 2wt% (particle size is 30nm).
[0117] Preparation method:
[0118] After vacuum drying barium titanate, the first barium sulfate and the second barium sulfate at 100° C. for 4 hours, the barium titanate, the barium sulfate, the silane coupling agent, nano silicon dioxide (with a particle size of 20 nm) and nano aluminum oxide (with a particle size of 30 nm) are mixed in a ball mill in proportion, the mixing time is 2 hours, the rotation speed is 160 rpm, and a uniform mixed material is obtained;
[0119] The obtained mixture was spray granulated by a spray granulator, the feed rate of the spray granulation was 15 mL / min, the spray drying temperature was 120°C, and spherical particles with a particle size of 180 μm were obtained, and the spherical particles were allowed to stand at room temperature for 24 hours;
[0120] The spherical particles were pressed into shape by isostatic pressing method, with a mold temperature of 40°C and a pressure of 320 MPa. The initial size of the mold was 412×824 mm, the molding time was 13 min, and compressed air was used to assist demoulding to obtain a green body.
[0121] The green body was placed on a support frame and placed in a sintering furnace. It was sintered in a nitrogen protective atmosphere at a sintering temperature of 1300°C and a holding time of 5 hours. After sintering, the temperature was cooled to room temperature at a cooling rate of 6°C / h. The surface was polished with 800-mesh fine sandpaper and precisely cut to a standard size of 400×800mm.
[0122] Performance Testing
[0123] The performance of the products of Examples 1 to 5 was tested according to the following testing standards:
[0124] 1. GB / T 1409-2006 "Measurement method for dielectric constant and loss tangent of electrical insulating materials": This standard specifies the measurement method for dielectric constant and loss tangent of electrical insulating materials. It is widely used in the determination of dielectric properties of various composite materials and is suitable for barium titanate-baryte composite materials.
[0125] 2. GB / T 5591.3-2018 "Electrical Insulating Materials Part 3: Test Methods": This standard provides test methods for insulating materials, especially detailed provisions on the test methods for dielectric loss, which are used for testing electrical insulating materials.
[0126] 3. GB / T 23913.1-2009 "Determination of shielding performance of radiation protection shielding materials": This standard covers the determination method of the shielding performance of radiation protection materials, and is particularly suitable for testing the shielding performance of shielding materials in X-ray and gamma ray environments.
[0127] 4. GB / T 7314-2017 "Method for compression test of metal materials at room temperature": This standard is applicable to the compression performance test of metal materials and composite materials at room temperature and the determination of the compressive strength of materials.
[0128] 5. GB / T 1449-2019 "Test method for flexural properties of fiber reinforced plastics": This standard is mainly used for the flexural properties test of fiber reinforced composites, and is suitable for the flexural properties test of barium titanate-baryte composites.
[0129] 6. GB / T 9966.3-2021 "Test methods for natural stone Part 3: Bulk density and water absorption": This standard specifies the determination method of bulk density and water absorption of stone materials, which is suitable for determining the density of composite materials.
[0130] 7. GB / T 23806-2020 "Determination method of fracture toughness of engineering ceramics": This standard provides a determination method for the fracture toughness of engineering ceramic materials, which is widely used in fracture toughness testing of high-performance ceramics and composite materials.
[0131] The results are shown in Table 2.
[0132] Table 2 Product performance of Examples 1 to 5
[0133]
[0134]
[0135]
[0136] It can be seen from Table 2 that the barium titanate-baryte composite material of the present invention has high dielectric constant, excellent radiation resistance and good mechanical strength, and is suitable for occasions requiring high dielectric constant and radiation resistance, such as radiation shielding plates, dielectric materials of electronic devices, etc.
[0137] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A barium titanate-baryte composite material, characterized in that: Including the following raw materials in percentage by weight: Barium titanate 20-30.5%, first barium sulfate 35-45%, second barium sulfate 25-35%, coupling agent, nano silicon dioxide 0.5-2%, nano aluminum oxide 0.5-2%; The average particle size of the first barium sulfate is 4 to 5 μm, and the maximum particle size is ≤27 μm; the average particle size of the second barium sulfate is 3 to 4.5 μm, and the maximum particle size is ≤24 μm; The coupling agent is a titanate coupling agent or a silane coupling agent; When the coupling agent is a titanate coupling agent, the mass percentage of the titanate coupling agent is 1 to 3%; When the coupling agent is a silane coupling agent, the mass percentage of the silane coupling agent is 0.5-2%.
2. The barium titanate-baryte composite material according to claim 1, characterized in that: The titanate coupling agent includes one or more of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, tetraoctyl titanate and tetraphenyl titanate.
3. The barium titanate-baryte composite material according to claim 1, characterized in that: The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, vinyltriethoxysilane, epoxypropyltrimethoxysilane and isocyanatepropyltriethoxysilane.
4. The method for preparing the barium titanate-baryte composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The barium titanate, the first barium sulfate, the second barium sulfate, the coupling agent, the nano silicon dioxide and the nano aluminum oxide are mixed by ball milling to obtain a mixed material; The mixed material is spray-granulated to obtain a spherical material; The spherical material is pressed and formed by isostatic pressing to obtain a green body; The green body is sintered in a protective atmosphere to obtain a barium titanate-baryte composite material.
5. The preparation method according to claim 4, characterized in that: The ball milling mixing time is 2 to 4 hours, and the rotation speed is 150 to 200 rpm.
6. The preparation method according to claim 4, characterized in that: The spray granulation conditions include: a feed rate of 10 to 20 mL / min and a spray drying temperature of 120 to 150°C.
7. The preparation method according to claim 4, characterized in that: The particle size of the spherical material is 100-300 μm.
8. The preparation method according to claim 4, characterized in that: The compression molding conditions include: a pressure of 250-350 MPa, a mold temperature of 20-40° C., and a time of 10-15 min.
9. The preparation method according to claim 4, characterized in that: The sintering temperature is 1250-1350° C., and the holding time is 4-6 hours; the protective atmosphere includes nitrogen or argon.
10. Use of the barium titanate-baryte composite material according to any one of claims 1 to 3 or the barium titanate-baryte composite material prepared by the preparation method according to any one of claims 4 to 9 in the fields of architectural decoration, industrial protection or electronic components.
Citation Information
Patent Citations
Polyamide composition for piezoelectric materials and preparation method
CN106751780A
Composite phase-change material, phase-change temperature-adjusting lightweight ceramic tile and preparation method of phase-change temperature-adjusting lightweight ceramic tile
CN118620580A
Modified polytetrafluoroethylene as well as preparation method and application thereof
CN118852883A
TH126329A